Effects of vigabatrin on partial seizures and cognitive function. Issue 9 (September 1994) - Grünewald, R A; Thompson, P J; Corcoran, R; Corden, Z; Jackson, G D; Duncan, J S
Abstract : Forty five patients with refractory partial seizures were studied in a prospective, randomised, placebo controlled, add on, parallel group, double blind trial of the new antiepileptic drug vigabatrin (1.5 g twice daily) followed by open treatment. Seizure frequency was monitored throughout an eight week baseline, 20 weeks double blind, and up to 18 months of open vigabatrin treatment. Cognitive function, including measures of memory and concentration, mood, and behaviour were assessed at baseline and again during the 20th week of treatment. Vigabatrin was associated with a significant reduction in a measure of motor speed and overall score on a design learning test in the first 20 weeks of treatment. In comparison with the baseline period, vigabatrin treatment was associated with a significant reduction in median complex partial seizure frequency four to 12 and 12 to 20 weeks after commencing vigabatrin (-66% and -69% in the vigabatrin group, +50% and +25% in the placebo group). Ten of 20 patients on vigabatrin and four of 23 on placebo showed a > 50% reduction in complex partial seizure frequency in the last eight weeks of double blind treatment. At least 60% of responders had maintained the response to vigabatrin when assessed during the open phase of the trial at 44 weeks. Two patients discontinued vigabatrin because of depression, which resolved on drug withdrawal.